Saline irrigation management in field conditions of a semi-arid area in Tunisia (Asian Journal of Agriculture, 2022)
Abstract. Daghari I, Daghari H, Ben Khalifa N,, Mahmoud M. 2022. Saline irrigation management in field conditions of a semi-arid area in Tunisia. Asian J Agric 6: 103-108. Tunisian saline soils occupy about 25% of the total irrigated area. The irrigated area of ??"Dyiar-Al-Hujjej" in Tunisia was considered because seawater intrusion took place and salinization of the aquifer reached a very high water electrical conductivity value of 15 dS/m in the 90s, which caused many local farmers to abandon land parcels and wells. In addition, salinity has reduced plant growth and water quality, leading to lower crop yields and degradation of stock water reserves. Excess salt affects overall soil health, reducing productivity. It kills plants, leaving bare soil prone to erosion. In this study, the electrical conductivity of the soil under several irrigated crops was evaluated for two soil layers (0-20 cm and 20-40 cm). Follow-up surveys of agricultural practices have shown that the irrigation water's quality has a considerable effect on the soil's electrical conductivity and, therefore, on the choice of crops. We also showed that crop rotation is a practice done by farmers to maintain and improve soil fertility by utilizing soil nutrient losses due to salinization. This study can be the basis of a valuation to allow farmers to have the best cultural practices to fight the salinization of their soils.
Keywords: Famers practices, irrigation, seawater intrusion, semi-arid, soil salinization